End-stage care for children after heart transplant - Everitt, Melanie D. (Frontiers in Transplantation, 2023)
Heart transplant is performed annually in over 600 children worldwide to treat life-limiting cardiac disease. Conversations regarding waitlist mortality, post-transplant morbidity and mortality, and goals of care are commonplace pre-transplant. However, there is a void of information and resources for providers and families when end-stage disease recurs in the long-term transplant recipient. The purpose of this review is to discuss the care of the pediatric heart transplant recipient with chronic cardiac dysfunction occurring years after a successful transplant. This includes a need for transplant providers to have education and training related both to palliative care and medical ethics to improve shared decision making with patients and families.